2016
DOI: 10.1158/2159-8290.cd-15-1408
|View full text |Cite
|
Sign up to set email alerts
|

PD-1hi Identifies a Novel Regulatory B-cell Population in Human Hepatoma That Promotes Disease Progression

Abstract: B cells often constitute abundant cellular components in human tumors. Regulatory B cells that are functionally defi ned by their ability to produce IL10 downregulate infl ammation and control T-cell immunity. Here, we identifi ed a protumorigenic subset of B cells that constitutively expressed higher levels of programmed cell death-1 (PD-1) and constituted ∼ 10% of all B cells in advanced-stage hepatocellular carcinoma (HCC).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
261
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(272 citation statements)
references
References 46 publications
9
261
1
1
Order By: Relevance
“…Studies in human peripheral blood and tumour tissue have identified CD24 high CD38 high and PD-1 high regulatory B cells, respectively, and it has been suggested that, upon encountering external stimulus, these cells regulate T-cell responses by releasing protumorigenic IL-10192035. In our investigation, the FcγRII low/− activated B cells, without additional stimulation, could secrete IL-10 to repress tumour-specific cytotoxic T-cell response.…”
Section: Discussionmentioning
confidence: 56%
“…Studies in human peripheral blood and tumour tissue have identified CD24 high CD38 high and PD-1 high regulatory B cells, respectively, and it has been suggested that, upon encountering external stimulus, these cells regulate T-cell responses by releasing protumorigenic IL-10192035. In our investigation, the FcγRII low/− activated B cells, without additional stimulation, could secrete IL-10 to repress tumour-specific cytotoxic T-cell response.…”
Section: Discussionmentioning
confidence: 56%
“…In this issue of Cancer Discovery , Xiao and colleagues present a comprehensive study on a novel PD-1 high regulatory B cell subset in human hepatocellular carcinoma (7). This newly identified subset of PD-1 high regulatory B cell is correlated with the tumor stage and early recurrence of patients.…”
mentioning
confidence: 99%
“…Expressed on normal tissues such as pancreas, colon, kidney tubules, bronchus, thyroid, and parathyroid glands [111]. …”
Section: Figurementioning
confidence: 99%
“…However, immunosuppressive tumor microenvironment undermines lymphocyte function. Myeloid derived suppressor cells [41], mesenchymal stem cells [117], regulatory T cells [108], cancer-associated fibroblasts [3], tumor associated macrophages [30], and programmed cell death protein 1 (PD-1) hi regulatory B cell [111] suppress immune cells and promote HCC progression. Furthermore, overexpression of inhibitory receptors including PD-1 and T cell immunoglobulin and mucin-domain containing-3 (TIM-3) on circulating or tumor-infiltrating T cells was associated with poor clinical outcomes [64, 100].…”
Section: Introductionmentioning
confidence: 99%